PENDAMPINGAN PENGEMBANGAN BAHAN AJAR INTERAKTIF BERBASIS TEKNOLOGI BAGI PENDIDIK PADA PENDIDIKAN NONFORMAL - Asri, Muhammad; Marzuki, Kartini; Latif, M Ali; Amir, Rudi; Natsir, Nasrah (Universitas Negeri Makassar, 2024)
The use of technology-based interactive teaching materials that are appropriate and easy to understand will help students understand the learning material, including students in non-formal education units. The main problem faced by partners is the low ability of tutors in non-formal education units to use technology-based teaching materials or interactive modules that can support the learning process to run smoothly and effectively and can improve learning outcomes to be more optimal in accordance with the era of digital technology use. This community service aims to introduce and create technology-based teaching materials or interactive modules using the Canva application for tutors at the Majena Regency Non-formal Education Unit, West Sulawesi. To achieve this goal, assistance is provided in creating interactive teaching materials using the Canva application, using lecture, discussion and practice methods. By implementing this PKM, tutors can increase their understanding and ability to create and use technology-based interactive teaching materials.